اثر الالعـاب بـدرس التربية الرياضـية في مستوى الاكتئاب النفسي لتلاميذ بطئي التعلم الطور الثالث - طابور, علي بديوي (Sulaimani Journal for Humanities, 2018)
The phenomenon of slow learning is still a concern for parents, teachers and students themselves, being a multi-faceted problem psychologically and socially, educational and health, which are basic in the primary stage, especially as it is the first stages of basic learning and because their diagnosis is at this stage, and the school is the educational institution that aims to provide the appropriate atmosphere for students Prepare them properly from different aspects as well as provide them with different learning skills And through the observation of the researcher to students slow learning and isolation from the rest of the members and not to participate actively in the lesson of physical education through the various motor performance of small games and physical exercises, which will reflect on their physical and psychological abilities and increase the level of psychological pressure, especially the case of psychological depression in the lesson of physical education, This problem and the development of appropriate solutions to ensure the development and growth of pupils slow learning in all areas, Therefore, the researcher decided to study this problem and develop suitable solutions to ensure the development and development of students slow learning in all areas. The experimental method was used and the sample of 26 students was divided into two groups, one experimental and one female. The research found that the use of small games and activities of motor education Has had a positive effect and a significant improvement in the level of depression.